Alteration of the centroid method to evaluate genotypic adaptability - Nascimento, Moysés; Cruz, Cosme Damião; Campana, Ana Carolina Mota; Tomaz, Rafael Simões; Salgado, Caio Césio; Ferreira, Reinaldo de Paula (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to modify the centroid method of evaluation of phenotypic adaptability and the phenotype stability of genotypes in order for the method to make greater biological sense and improve its quantitative and qualitative performance. The method was modified by means of the inclusion of three additional ideotypes defined in accordance with the genotypes' average yield in the environments tested. The alfalfa (Medicago sativa L.) forage yield of 92 genotypes was used. The trial had a randomized block design, with two replicates, and the data were used to test the method. The genotypes underwent 20 cuts, from November 2004 to June 2006. Each cut was considered an environment. The inclusion of ideotypes of greater biological average production in the environments produced an arrow-shaped graphical dispersion directed to the right in which the most productive genotypes were placed near the tip of the arrow. With the alteration only five genotypes were classified into the former classes of the original centroid method. The arrow-shaped figure allowed a direct comparison of genotypes throughout the productivity gradient. The alteration performed in the method preserved the easy interpretation of results for genotype recommendations of the original method, and does leaves no room for ambiguity in interpretation of the results.